1972
DOI: 10.1073/pnas.69.3.717
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene: A Natural Regulator of Sex Expression of Cucumis melo L

Abstract: Sex expression in cucumber (Cucumis sativus L.) and muskmelon (C. melo L.) was correlated with endogenous ethylene production. Plants of gynoecious (all female) sex types of the two species produced more ethylene than monoecius (male-female) plants. Sex expression in cucurbits is influenced by genetic, environmental, and hormonal factors. Monoecious strains of cucumber (Cucumis sativus L.) and muskmelon (C. melo L.) bear staminate (male) and pistillate (female) flowers. Gynoecious strains normally produce only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
0
4

Year Published

1973
1973
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 14 publications
6
70
0
4
Order By: Relevance
“…Byers et al (1972) found that treating monoecious cucurbits with ethylene or compounds that promote ethylene synthesis causes earlier production of pistillate flowers, that is, promote feminization. They found that application of GA 3 promotes masculinization in cucumber gynoecious plants, but not in melon gynoecious plants.…”
Section: Resultsmentioning
confidence: 99%
“…Byers et al (1972) found that treating monoecious cucurbits with ethylene or compounds that promote ethylene synthesis causes earlier production of pistillate flowers, that is, promote feminization. They found that application of GA 3 promotes masculinization in cucumber gynoecious plants, but not in melon gynoecious plants.…”
Section: Resultsmentioning
confidence: 99%
“…Plants are gynoecious if the genotype is A-gg, monoecious if the genotype is A-G-, hermaphrodite if the genotype is aagg, and andromonoecious if the genotype is aaG- (Kenigsbuch and Cohen, 1990). It is known that ethylene inhibitors induce the formation of bisexual flowers in gynoecious melon plants (Byers et al, 1972), which is why ethylene is considered to inhibit stamen development in melon plants. Recently, it was reported that the A gene encodes ACC synthase and was designated CmACS-7.…”
Section: Discussionmentioning
confidence: 99%
“…However, flowering and its ratio can me modulates by phytohormones in cucurbits [32] which could be tested as a cheaper alternative. Future attempts in hydroponic "Loche" production should consider external application of ethylene or ethylene-releasing compounds in well-stablished transplants as for melon [33] and cucumber [34] and/or direct modulation of any of the genes involved in sex determination for cucurbits already identified [35,36]. The former only probable if the parthenocarpic origin of the fruit is validated [6] since no male flowers might be obtained.…”
Section: Discussionmentioning
confidence: 99%